Supply Chain Strategy for Implementing Fiscal Decentralization and its Effect on Regional Performance in North Sumatera Province, Indonesia - Sirojuzilam Sirojuzilam; Edo Billy Andri Turnip; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this study is to investigate the supply chain strategy for implementing fiscal decentralization and its effect on regional performance which consists of financial equalization capabilities and regional development in North Sumatera province, Indonesia. A secondary data collected from the Central Bureau of statistic North Sumatera which consist of 33 regencies/cities in North Sumatera province for the period of 2011-2015 and analyzed using panel regression analysis by assisting EVIEWS 10.0.  This study applied the Williamson index to identify the effect of fiscal decentralization of financial capability via the General Allocation Fund (DAU) budget per capita and Gross Regional Domestic Product (GRDP). The variable of fiscal decentralization is the primary revenue received by local government measured by Original Local Government Revenue (PAD) and Balance Fund (DP) while the regional performance using per capita income. The result of the analysis shows that the random effect model is the best model for estimating the effect of fiscal decentralization on regional performance. By applying the Williamson Index for General Allocation Fund per capita, this study indicates it unstably distributed. Also, Williamson Index for per capita income distribution categorized as moderate. Lastly, the Original Local Government Revenue and Balance Fund have a positive effect on regional performance.